The Influence of Marketing Margins, Production Cost, and Labor Productivity on Farmers’ Welfare: A regression analysis - Maria Uriel Cifra; James Mark Lee; Carlo Miguel Vizcarra; Peter Jeff Camaro (Faculty of Science and Technology University of Pramita Indonesia, 2022)
Farmers encounter difficulties gaining real profit due to the inequalities brought by the middlemen-centric agricultural system, depreciating their overall welfare. Middlemen are contributors to a lengthened supply chain; hence, profit margins absorbed by middlemen are higher compared to farmers. Production costs are also integral to production, with long-run growth associated with lowering production costs. Efficiency in labor productivity of the agricultural sector is attained through the improvement of systems, which in turn yields crop profitability for farmers. The purpose of this research was to analyze the influence of middlemen, production costs, and labor productivity on farmers' welfare in the agricultural sector of the Philippines since local studies are scarce concerning middlemen and farmers and also to provide additional information for the policymakers in terms of the decision-making process to identify the farmers' dilemma and develop a policy that would help improve farmers' welfare. The approach used in this research was quantitative. The study used a multiple regression model to determine the effects of exogenous variables on Farmers' Welfare. The researchers used farmers' wages as a proxy variable for farmers' welfare. The results showed that Marketing Margins depreciate Farmers' Welfare due to lower income received by the middlemen caused by the broader gap between the farm gate price and consumer price from the marketing channel. It is also found that production cost has a negative significance on farmers' welfare showing that there are inefficiencies in farmers' production such as technical and allocative inefficiencies. Lastly, Labor Productivity increases farmers' income by efficiently allocating resources such as human resources and using land plots instead of overspending on inputs.